Chhatris (memorial structures) flanking the Chandrabhaga River - Temples of India Project Team (Jio Institute, 2024)
On the southern end of the Chandrabhaga temple complex, there is a ghat (bank) that has a few chhatris (memorial structures) and a few loose sculptures flanking the Chandrabhaga River. The devotees take a dip in the river, especially in the auspicious month of Kartik (October–November) and light diyas (oil lamps) in the temple and under the banyan tree.